Socioeconomic circumstances and the risk of bowel cancer in Northern Ireland. Issue 6 (December 1996) - Kee, F; Wilson, R; Currie, S; Sloan, J; Houston, R; Rowlands, B; Moorehead, J
Abstract : OBJECTIVE: To describe the variation in the incidence of colorectal cancer across Northern Ireland and relate it to factors associated with community deprivation. DESIGN: This was a cross sectional descriptive study. SETTING: Incidence data were obtained from a population based register for the period 1990-91. Small areas were characterised by their "affluence", or lack of it, by deriving a Townsend deprivation score for each electoral ward, using information from the 1991 census. PARTICIPANTS, MAIN OUTCOME MEASURES, AND STATISTICAL METHODS: The age standardised incidence was calculated for all colorectal cancer cases diagnosed histologically in 1990-91. Electoral wards were grouped into quintiles of the population after ranking of their Townsend scores and the association with incidence was studied using Poisson regression. RESULTS: The age standardised colorectal cancer incidence ranged from 22.5 (for quintile 1) to 29.9/100, 000 (quintile 5) for men but the trend for women was less regular and rates were 18.4, 23.8, 27.3, 26.5, and 23.9/100, 000 for quintiles 1-5 respectively (that is, from the most "affluent" to the most "deprived" fifths of the population). After adjusting for age and sex in Poisson regression, there was a significant association between the total colorectal cancer incidence and levels of community deprivation. The rate ratio for the most deprived quintile of the population (compared with the least) was 1.28 (95% CI 1.06, 1.53). The effect was stronger for rectal cancer than for colonic cancer. There was no association between community deprivation and the cancer stage at diagnosis. CONCLUSIONS: In this population, the colorectal cancer incidence is associated with the level of material deprivation. The disease stages at the time of diagnosis in patients from more deprived areas seem to be comparable with those of patients from affluent areas. As others have shown, associations such as these are not explicable entirely on the basis of the distribution of known risk factors. Further research is needed to determine plausible mechanisms for the association.